2008
DOI: 10.1007/s11695-008-9583-y
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Carbohydrate Intake and Weight Loss After Bariatric Surgery

Abstract: The glycemic load and grams of carbohydrate are intake factors that can be useful tools in weight loss and long-term weight maintenance on patients who have undergone Roux-en-Y Gastric Bypass (RYGB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 37 publications
1
38
0
3
Order By: Relevance
“…However, little is known about the associations between changes in total energy intake and energy-contributing nutrients (i.e., the macronutrients carbohydrates, fat, and protein) and the long-term weight change in patients who have undergone bariatric surgery (14). Most studies have been based on few participants (n , 100) (7,(15)(16)(17)(18), short follow-ups (,3 y) (7,17,19), and only postsurgery dietary intakes (4,7,8,15,16,18). Thus, in most studies, it has not been possible to analyze the changes between dietary intakes before and after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the associations between changes in total energy intake and energy-contributing nutrients (i.e., the macronutrients carbohydrates, fat, and protein) and the long-term weight change in patients who have undergone bariatric surgery (14). Most studies have been based on few participants (n , 100) (7,(15)(16)(17)(18), short follow-ups (,3 y) (7,17,19), and only postsurgery dietary intakes (4,7,8,15,16,18). Thus, in most studies, it has not been possible to analyze the changes between dietary intakes before and after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of calorie intake is objective of dietetic treatment at the obesity and postoperative of the bariatric surgery 26 and it is associated with weigh loss at the postoperative at long time 20 . Study has showed a calorie intake around 1500 kcal at individuals with 3 to 4 years bariatric surgery.…”
Section: Competing Interestsmentioning
confidence: 99%
“…According Faria et al 20 patients postbariatric that realized high intake of lipids and carbohydrates According to the nutritional pyramid proposed for population this study, the writer made a division in food groups, which the groups elaborated for him are: "high protein, low fat foods", "high fiber, low calorie foods", "grains and cereals", and "high calorie foods, fat and sweets are energy dense foods". The consumption of foods group "high protein, low fat foods" was adequate, but the groups "high fiber, low calorie foods" and "grains and cereals" showed upper of recommendation.…”
mentioning
confidence: 99%
“…Leite y cols 7 , evaluaron la influencia de la composición de la dieta postoperatoria en el proceso de descenso de peso. Se calculó el promedio de baja de peso mensual, se analizó la frecuencia de consumo de alimentos y la proporción de los diferentes macronutrientes (lípidos, proteínas y carbohidratos) que los pacientes incluían en su dieta después del BPG.…”
Section: Reducción Del Pesounclassified
“…El consumo frecuente de carbohidratos se asocia a una mayor ganancia de peso 7 . Independiente de su aporte calórico, los azúcares y alimentos de mayor índice glicémico estimulan la producción de insulina y disminuyen la lipolisis.…”
Section: Reganancia De Pesounclassified